Effect of smoking on reproductive hormones and semen parameters of infertile Saudi Arabians - Haifa A Al-Turki (Urology Annals, 2015)
Objective: The purpose of this retrospective study is to look into the effect of smoking on semen and hormonal profile of Saudi Arabians attending infertility clinics. Materials and Methods: Medical record numbers of patients who attended infertility clinics and who underwent full assessment were identified rom Quadramed system and out-patient log books between January 2010 and December 2012. The standard protocol of the patients include full history, age, number of years of marriage personal habits of smoking, alcohol consumption, primary or secondary infertility. Standard laboratory tests which were performed, included, complete blood picture, random blood sugar, testosterone, follicle stimulation hormone, luteinizing hormone, prolactin level and semen analysis; volume, count, progressive motility and morphology. The data was entered in the database and analyzed. Results: During the study period, 279 patients attended and infertility clinic and only 258 gave the sample for analysis. The average age of patients in the smoking group was 34.23 ± 7.66 and in the nonsmokers 34.07 ± 7.92 years. Primary infertility was more common in smokers versus nonsmokers P < 0.001 confidence interval (CI)< −44.0705, total serum testosterone level was lower 383.8 ± 239.5 versus 422.5 ± 139.2 ng/dL (0.009 CI< −9.9415), serum prolactin level was higher 18.68 ± 13.28 versus 12.85 ± 12.34 ng/mL (0.001 CI < 8.3794). The average volume of the semen among the smokers was 2.8 ± 1.35 mL and in nonsmokers it was 3.08 ± 0.76 mL (P < 0.008 CI< −0.123). The mean progressive motility in smokers was 31.5 ± 23.1 compared to nonsmokers 40.05 ± 25.43% (0.002 CI< −3.2962) and total sperm count was 119.52 ± 114.12 and 139.71 ± 104.82 million/mL (0.07 CI < 1.4657). Conclusions: This study shows that the effect of smoking is dramatic reduction in the hormonal levels and semen parameters. It is recommended that smoking men undergoing fertility treatment should stop smoking to increase their chances of having offspring.